2022
DOI: 10.1136/bmjopen-2022-063622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary cytology, primary HPV testing and co-testing as cervical cancer screening for Chinese women: a population-based screening cohort

Abstract: ObjectivesWe compared clinical performance of three strategies of primary human papillomavirus (HPV) testing, primary cytology and co-testing for cervical cancer screening.DesignA population-based prospective cohort study of clinical performance of screening strategy.SettingPatients recruited from community in Changzhi County, Shanxi Province, China.Patient3209 women aged 30–64 years without gynaecological issues.Primary and secondary outcome measuresThe performance of different screening strategies for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…First, our findings suggest that the age-standardized abnormality rates of primary screening results were significantly higher for HPV-based screening compared with cytology. This supports the conclusion that the HPV-based method is more sensitive than cytology as a primary screening method, could detect more people with suspicious cervical lesions and reduce the rate of underdiagnosis [26,27]. Second, the proportion of abnormal colposcopy results following HPV-based primary screening was also much higher than that of cytology, indicating that HPV testing combined with genotyping and cytology triage for primary screening has higher accuracy, which may relatively improve the benefit of colposcopy in cases where there is a higher colposcopy referral rate for HPV-based testing [28,29].…”
Section: Real-world Effectiveness Of Different Strategies and Problem...supporting
confidence: 80%
“…First, our findings suggest that the age-standardized abnormality rates of primary screening results were significantly higher for HPV-based screening compared with cytology. This supports the conclusion that the HPV-based method is more sensitive than cytology as a primary screening method, could detect more people with suspicious cervical lesions and reduce the rate of underdiagnosis [26,27]. Second, the proportion of abnormal colposcopy results following HPV-based primary screening was also much higher than that of cytology, indicating that HPV testing combined with genotyping and cytology triage for primary screening has higher accuracy, which may relatively improve the benefit of colposcopy in cases where there is a higher colposcopy referral rate for HPV-based testing [28,29].…”
Section: Real-world Effectiveness Of Different Strategies and Problem...supporting
confidence: 80%
“…Studies showed that both HPV testing and cytology increased the sensitivity and specificity of CC screening while lowering false-positive cases [55], with the potential to lower the rates of diagnostic inconsistencies [17]. This, in turn, ensures that most CCs will be detected during subsequent diagnosis [56,57]. The integration of cytology and HPV genotyping detection offers a more efficient approach to assessing the morbidity risks associated with cervical CIN II and III lesions [30].…”
Section: Discussionmentioning
confidence: 99%
“…72 There are now three alternatives that are advised for CC screening for those between the ages of 21 and 65: primary HPV testing every 5 years, cytology alone every 3 years, and co-testing with the combination of cytology and HPV testing every 5 years. 73,74 Primary HPV testing and co-testing are more successful than cytology alone in identifying high-grade cervical intraepithelial neoplasia in individuals aged 25-65 who are at moderate risk.…”
Section: Hiv Infectionmentioning
confidence: 99%